2020
DOI: 10.1186/s12903-020-01274-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene habits and possible transmission of COVID-19 among cohabitants

Abstract: Background To find out whether misuse of dental hygiene, in terms of certain dental habits, may facilitate the spread of COVID-19 among cohabiting individuals. Methods 302 COVID-19 infected (PCR +) subjects cohabiting with someone else at home were selected for an observational cross-sectional study. An anonymous online questionnaire was developed using Google forms to avoid person-to-person contact. The structured questionnaire consisted of questions covering several areas: sociodemographic data, cross tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 20 publications
0
18
0
17
Order By: Relevance
“…Desse modo, podem-se inferir as seguintes relações: Medidas como a desinfecção da cabeça da escova após o uso pode ser realizada com iodopovidona a 0,2% (KAMPF et al, 2020) que diminui a transmissibilidade da infecção entre coabitantes. Além disso, recomenda-se que o mesmo tubo de pasta de dentes também não deve ser usado entre membros da mesma família, pois essa é outra forma de facilitar a contaminação cruzada (GONZÁLEZ-OLMO et al, 2020). Também é necessário armazenar a escova com a cabeça para cima, uma vez que facilita a secagem mais rápida e dificulta a disseminação de microrganismos (MEDRANO-FÉLIX et al, 2011;KESHAV et al, 2015;MAILLARD et al, 2020).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Desse modo, podem-se inferir as seguintes relações: Medidas como a desinfecção da cabeça da escova após o uso pode ser realizada com iodopovidona a 0,2% (KAMPF et al, 2020) que diminui a transmissibilidade da infecção entre coabitantes. Além disso, recomenda-se que o mesmo tubo de pasta de dentes também não deve ser usado entre membros da mesma família, pois essa é outra forma de facilitar a contaminação cruzada (GONZÁLEZ-OLMO et al, 2020). Também é necessário armazenar a escova com a cabeça para cima, uma vez que facilita a secagem mais rápida e dificulta a disseminação de microrganismos (MEDRANO-FÉLIX et al, 2011;KESHAV et al, 2015;MAILLARD et al, 2020).…”
Section: Resultsunclassified
“…Ao final de um eventual processo infeccioso, é necessário ter cautela e utilizar uma nova escova. A detecção do SARS-CoV-2 e de uma alta carga viral no escarro de um paciente convalescente levanta preocupações sobre a potencial transmissibilidade após a recuperação (GONZÁLEZ-OLMO et al, 2020).…”
Section: Resultsunclassified
“…26 It is essential to emphasize that in the context of COVID-19, some patients did not show any symptoms during the early stage of infection, 27,28 and infected subjects can spread the disease even before developing symptoms [29][30][31] through infected saliva. [32][33][34] Recently, González-Olmo et al 4 have found that 3% of cohabitants share toothbrushes, 64.2% used the same toothbrush container, and 50.3% the same toothpaste, suggesting that inadequate measures and habits could indirectly contribute to COVID-19 infection between people living together. 4 Regarding the disinfection and storage of toothbrushes, no experimental studies were found related to SARS-CoV-2 infection.…”
Section: Scielomentioning
confidence: 99%
“…[32][33][34] Recently, González-Olmo et al 4 have found that 3% of cohabitants share toothbrushes, 64.2% used the same toothbrush container, and 50.3% the same toothpaste, suggesting that inadequate measures and habits could indirectly contribute to COVID-19 infection between people living together. 4 Regarding the disinfection and storage of toothbrushes, no experimental studies were found related to SARS-CoV-2 infection. However, concerning other viruses, Devine et al 35 demonstrated that tetrasodium EDTA reduces Herpes simplex virus and poliovirus infectivity, suggesting its use to neutralize enveloped and nonenveloped viruses on dental appliances.…”
Section: Scielomentioning
confidence: 99%
“…6 Inappropriate measures in dental hygiene contribute to the transmission of COVID-19 between cohabitants indirectly. 7 Half of the students brushed their teeth twice daily. 8 Programs for oral health promotion are required to improve knowledge and practices regarding oral hygiene among pupils.…”
mentioning
confidence: 99%